Involvement of CD147 on multidrug resistance through the regulation of P-glycoprotein expression in K562/ADR leukemic cell line - Aoranit Somno (2018)
© 2016 The Authors The relationship between P-gp and CD147 in the regulation of MDR in leukemic cells has not been reported. This study aimed to investigate the correlation between CD147 and P-gp in the regulation of drug resistance in the K562/ADR leukemic cell line. The results showed that drug-resistant K562/ADR cells expressed significantly higher P-gp and CD147 levels than drug-free K562/ADR cells. To determine the regulatory effect of CD147 on P-gp expression, anti-CD147 antibody MEM-M6/6 significantly decreased P-gp and CD147 mRNA and protein levels. This is the first report to show that CD147 mediates MDR in leukemia through the regulation of P-gp expression.